Sistem Pakar Diagnosa Penyakit Hewan Ternak Menggunakan Metode Rule Based Expert System - Mutiara NR Ge'e; Mutiara NR Ge’e; Roito Siburian; Rut F Manalu3; Melissa P Hutabarat; Adira Arifandi; M. Rizky (Interaksi : Jurnal Informatika Dan Teknologi Sistem Informasi, 2026)
Livestock health is a crucial factor in maintaining the productivity and sustainability of the livestock sector. The limited availability of veterinary medical personnel, particularly in rural areas, prevents the rapid and accurate diagnosis of livestock diseases. This situation encourages the use of technology as a tool for early disease identification. Cattle, as a livestock commodity with high economic value in Indonesia, are reportedly susceptible to various diseases, such as three-day fever, diarrhea, mastitis, and foot-and-mouth disease (FMD), which can reduce productivity. This article was compiled using a literature review method, reviewing several previous studies that discussed the application of rule-based expert systems in cattle disease diagnosis. The study focuses on the concept of expert systems, forward chaining reasoning methods, and their potential application as decision support systems in the field of livestock health. The results are expected to provide an overview and serve as an initial reference for the development of future livestock health support systems.